Current theoretical methods applied to study cyclodextrins and their complexes - Castro, Eduardo Alberto (2002)
This review deals with the description of current theoretical methods tostudy chemical and physical chemistry properties of cyclodextrins and their complexes. This study covers from 1998 to present, with the exception of some papers not included in a rather recent review. Five thematic areas were chosen to organize the informdion: computational studies of host-guest compounds, computational studies for interpreting spectral data, free energy simulations, enantiomers separation, and quantitative structureactivity (property) relationships.